Experimental investigation of a super performance dew point air cooler - Xu, Peng; Ma, Xiaoli; Zhao, Xudong; Fancey, Kevin (Applied energy, 2017)
This paper presents an experimental investigation of a super performance dew point air cooler which, by employing a super performance wet material layer, innovative heat and mass exchanger and intermittent water supply scheme, has achieved a significantly higher energy efficiency (i.e. Coefficient of Performance, COP) and a much lower electrical energy use compared to the existing air coolers of the same type. This involves the dedicated system design & construction, fully planned experimental testing under various simulated climatic conditions representing the climate of hot & dry, warm & dry, moderate, warm & humid and standard lab testing condition, testing results analysis and discussion, as well as the parallel comparison against the commercial dew point air cooler. Under the standard test condition, i.e. dry bulb temperature of 37.8 °C and coincident wet bulb temperature of 21.1 °C, the prototype cooler achieved the wet-bulb cooling effectiveness of 114% and dew-point cooling effectiveness of 75%, yielding a significantly high COP value of 52.5 at the optimal working air ratio of 0.364. The testing also indicated that the lower inlet air relative humidity led to a higher cooling efficiency, while the lower cooling output helped increase COP and cooling effectiveness (including the wet-bulb effectiveness and dew-point effectiveness) of the cooler.
Keywords: General Energy; Mechanical Engineering; Civil and Structural Engineering; Management; Monitoring; Policy and Law; Building and Construction